Using Metaphor in Cognitive Behavioral Therapy - Selim PİSTOF; Esat SANLI (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: Cognitive therapy is a method of psychotherapy used to treat many psychological and psychiatric disorders and is based on cognitive model of emotional disorders. Throughout the therapy, it is important for the clients to be trained in their problems and to perceive the fact which is one of the fundamental actions of cognitive behavioral therapy, that the emotional state interacts not only with in the thoughts, but also physical functions and environment. . Besides employing cognitive behavioral methods and techniques to overcome clients’ problems, cognitive therapy is also an educational process that eventually aims to teach the patient to be his own therapist. If the methods and techniques of the therapy used during the process are clear and easy for the patients to understand, the therapeutic benefits will increase. For this reason, effectiveness of cognitive behavioral therapy depends on to a great extent both how much the client understands the therapist and how proper language and metaphors are used by the therapist while having therapeutic relations. In this sense, the metaphor is a method which makes it easy for the clients to perceive some abstract and the concepts which seem to the client complex. In this study, the situations in which metaphor is used for therapy have been dealt under nine headings. Objective: We have dealt with the concepts, in a metaphorical context, such as explanation of irrational and rational beliefs, which will be studied in the later stages of the therapy, explaining cognitive model and the characteristics of the therapy. Conclusion: This review can be considered as a start and a guide to researchers who want to do comprehensive studies about this subject.